Biophysical Determinants and Constraints on Sperm Swimming Velocity - Carl D. Soulsbury; Stuart Humphries (Cells, 2022)
Over the last 50 years, sperm competition has become increasingly recognised as a potent evolutionary force shaping male ejaculate traits. One such trait is sperm swimming speed, with faster sperm associated with increased fertilisation success in some species. Consequently, sperm are often thought to have evolved to be longer in order to facilitate faster movement. However, despite the intrinsic appeal of this argument, sperm operate in a different biophysical environment than we are used to, and instead increasing length may not necessarily be associated with higher velocity. Here, we test four predictive models (ConstantPower Density, Constant Speed, Constant Power Transfer, Constant Force) of the relationship between sperm length and speed. We collated published data on sperm morphology and velocity from 141 animal species, tested for structural clustering of sperm morphology and then compared the model predictions across all morphologically similar sperm clusters. Within four of five morphological clusters of sperm, we did not find a significant positive relationship between total sperm length and velocity. Instead, in four morphological sperm clusters we found evidence for the Constant Speed model, which predicts that power output is determined by the flagellum and so is proportional to flagellum length. Our results show the relationship between sperm morphology (size, width) and swimming speed is complex and that traditional models do not capture the biophysical interactions involved. Future work therefore needs to incorporate not only a better understanding of how sperm operate in the microfluid environment, but also the importance of fertilising environment, i.e., internal and external fertilisers. The microenvironment in which sperm operate is of critical importance in shaping the relationship between sperm length and form and sperm swimming speed.